Determinación mediante inmunohistoquímica de la acción directa del Virus de la Inmunodeficiencia Felina en el sistema nervioso de gatos infectados naturalmente - Passeri, M.C. (2021)
The Feline Immunodeficiency Virus is used as a model for the study of infections by other lentiviruses, such as Human Immunodeficiency. It promotes a progressive and chronic immunodeficiency mainly due to the depletion of TCD4 + Lymphocytes. This disease has been extensively investigated but in experimentally infected cats. In this study, the neurological picture produced by the Feline Immunodeficiency Virus has been evaluated in a natural way and in the stage of asymptomatic carrier without opportunistic infections. This phase was chosen because in it the virus has a slow growth and the patients present an immune system not yet very damaged. In cats with feline immunodeficiency in the asymptomatic carrier stage with neurological signs that died, a necropsy examination was performed, taking samples from the central nervous system. Histopathology revealed encephalitis with a mild lymphoplasmacytic infiltrate and the Feline Immunodeficiency Virus was identified by immunohistochemistry, not only in the glia cells but also in the neurons. Immunohistochemistry demonstrated the presence of the virus located in relation to the histopathological lesions found in the central nervous system, this would demonstrate that the lesions are due to Feline Immunodeficiency Virus.